Analysis of Potential Threats to the Critical Infrastructure of the 31st Tactical Air Base, in the Context of the Security of the Poznan Agglomeration - Geppert, Karol; Konieczny, Jerzy (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The main purpose of the article is an attempt to analyze the potential threats to the critical infrastructure of the 31st Tactical Air Base in Poznań-Krzesiny in terms of the security of the Poznań agglomeration. The main threats that may occur have been indicated in the context of military, non-military, asymmetric or hybrid activities. In addition, the mortgage effects of the actions taken, which can have a measurable impact on the safety of the Poznań agglomeration, were discussed and presented. An additional thread in the article is the indication of the existing threats that took place in the area of the Poznań-Krzesiny military airport, which could threaten the functioning of the critical infrastructure located in the area of the 31st Tactical Air Base and the critical infrastructure located in the area of the Poznań agglomeration. The article does not contain any information or data defined as classified information in accordance with Ustawa z dnia 5 sierpnia 2010 r. o ochronie informacji niejawnych. Głównym celem artykułu jest próba analizy potencjalnych zagrożeń infrastruktury krytycznej 31. Bazy Lotnictwa Taktycznego w Poznaniu-Krzesinach w aspekcie bezpieczeństwa aglomeracji poznańskiej. Wskazano główne zagrożenia mogące wystąpić w kontekście podjęcia działań o charakterze militarnym, niemilitarnym, a także o charakterze asymetrycznym lub hybrydowym. Ponadto omówiono i przedstawiono hipotetyczne skutki podejmowanych działań, które w wymierny sposób mogą wpłynąć na bezpieczeństwo aglomeracji poznańskiej. Dodatkowym wątkiem w artykule jest wskazanie zaistniałych zagrożeń, jakie miały miejsce w rejonie lotniska wojskowego Poznań-Krzesiny, a które mogły zagrażać funkcjonowaniu infrastruktury krytycznej zlokalizowanej na terenie 31. Bazy Lotnictwa Taktycznego oraz infrastruktury krytycznej znajdującej się w obszarze aglomeracji Poznańskiej. W artykule nie umieszczono żadnych informacji ani danych definiowanych jako informacja niejawna, zgodnie z Ustawą z dnia 5 sierpnia 2010 r. o ochronie informacji niejawnych.
Analiza potencjalnych zagrożeń infrastruktury krytycznej 31 Bazy Lotnictwa Taktycznego, w kontekście bezpieczeństwa aglomeracji poznańskiej
Keywords: critical infrastructure; military airport; threat; security; urban agglomeration; Air Base; Armed Forces; infrastruktura krytyczna; lotnisko wojskowe; zagrożenie; bezpieczeństwo; aglomeracja miejska; Baza Lotnicza; Siły Zbrojne